Combating sars-cov-2 through lipoxins, proteasome, caveolin and nuclear factor-?b pathways in non-pregnant and pregnant populations - Celik, Onder; Celik, Nilufer; Aydin, Suleyman; Baysal, Bora; Aydin, Suna; Saglam, Aylin; Ersahin, Aynur A. (C M B Assoc, 2020)
It can be misleading to think that the new severe acute respiratory-syndrome coronavirus (SARS-COV2) which has a very strong mutation and adaptation capabilities, uses only the angiotensin-converting enzyme II (ACE2) pathway to reach target cells. Despite all the precautions taken, the pandemic attack continues and the rapid increase in the number of deaths suggest that this virus has entered the cell through different pathways and caused damage through different mechanisms. The main reason why the ACE2 pathway comes to the fore in all scientific studies is that this receptor is located at the entry point of basic mechanisms that provide alveolo-capillary homeostasis. SARS-CoV-2 has to use nuclear factor-kappa B (NF-kappa B), caveloae, clathrin, lipoxin, senile protease and pro-teasome pathways in addition to ACE2 to enter the target cell and initiate damage. For this reason, while new drug development studies are continuing, in order to be beneficial to patients in their acute period, it is imperative that we are able to come up with drugs that activate or inhibit these pathways and are currently in clinical use. It is also critical that we adopt these new pathways to the treatment of pregnant women affected by SARS-CoV-2, based on the scientific data we use to treat the general population.
Keywords: SARS-CoV-2; ACE2; Viral entry pathways; Nuclear factor-kappa B; Proteasome; Lipoxin; Off label drugs; Serine protease